PENGARUH PENGGUNAAN STRATEGI SEPAK BOLA VERBAL DENGAN MEDIA KARTU SOAL TERHADAP HASIL BELAJAR SISWA PADA MATERI SISTEM PENCERNAAN KELAS XI MIA SMAN 1 TINAMBUNG KABUPATEN POLEWALI MANDAR - Nur Ainun Fadhliana; Muh. Rapi; Ahmad Ali (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2019)
This study aims at (1) knowing student learning outcomes in digestive system material using Verbal Soccer Strategy (2) knowing student learning outcomes in digestive system material using Media Card Problem (3) knowing the effect of using Verbal Soccer Strategy with Media Cards Problem with results student learning in the digestive system material class XI MIA SMAN 1 Tinambung Polewali Mandar district. This research is a Quasi-Experimental type with the research design used is the Nonequivalent Control Group Design. The population in the study were all students of class XI MIA SMAN 1 Tinambung, amounting to 123 people in 4 classes. The research sample consisted of 58 people selected from two classes using thetechnique Multi-Stage Random Sampling. Data collection techniques using research instruments in the form of multiple choice tests as many as 20 questions. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis with a paired sample t-test. The results showed the average learning outcomes of students taught using verbal soccer strategies of = 75.69 while the average learning outcomes of students taught using question card media amounted to = 50.34. Inferential analysis results obtained by the value of F.arithmetic (0,000) <F.table (0,05). This shows that there is a positive and significant effect of using verbal soccer strategies with question card media on student learning outcomes in digestive system material class XI MIA SMAN 1 Tinambung Polewali Mandar Regency.